Identifying features in solid modelling - Várady, Tamás; Gaál, Balázs; Jared, Graham E.M. (Computers in industry, 1990)
In solid modelling parts of the object and separated objects need to be identified in order to perform operations and interrogate geometric data. The region of interest, which is often called a feature, may vary from a simple geometric element to a component in an assembly. In this paper the subject and the purpose of identifying features are described, together with four basic techniques of labelling, naming, topological expressions and geometric selection. The benefits and deficiencies of each technique are also presented concerning their use in interactive or batch environment. The general considerations are followed by examples from the build/ffsolid modeller, where all four identification techniques have been implemented and extensively used. An algorithm for efficiently selecting planar and curved faces of an object is also described.